The Effect of Ablution on Changes Blood Pressure in The Elderly with A History of Hypertension at Ibnu Sina Hospital - Rahmawati, -; M E, Rachman; Nurhikmawati, -; Irmayanti, -; A N W, Ningsih (International Journal of Human and Health Sciences (IJHHS), 2024)
Objective: To find out the effect of ablution on changes in blood pressure in the elderly with a history of hypertension at Ibnu Sina Hospital. Methods: Seeing changes in blood pressure drop momentarily in hypertensive patients before and after ablution, with data collection carried out at one time. Then, it is carried out through the "one group pretest and post-test design" in elderly with history of hypertension at Ibnu Sina Hospital. Results: There was a significant decrease with p value= 0.001 in systole and p value= 0.029 in diastole. The decrease occurs starting at the 5th minute of both systole and diastole, especially at the 15th minute. Mean value of difference in blood pressure before and after ablution at 5 minutes (systole 6.20 mmHg, diastole 4.70 mmHg), at 10 minutes (systole 11.57 mmHg, diastole 9.40 mmHg), at 15 minutes (systole 15.03 mmHg, diastole 11.53 mmHg). Conclusion: There was a decrease in blood pressure shortly after ablution in elderly people with hypertension. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S64